Peradaban Islam Di Nusantara Masa Digital Dan Perkembangan Pendidikannya - Siti Amalia; Siti Nur Melinda; M.Anang Sholikhudin (-, 2026)
The education system, including Islamic Religious Education (PAI), has undergone majorchanges due to the digital transformation that occurred during the Industrial Revolution 4.0. This article examines the prospects and difficulties associated with the advancement of Islamic Religious Education. curriculum and learning methods in the digital era. This study uses a qualitative descriptive methodology and a literature study method to investigate how digitalization affects learning interactions, educator readiness, infrastructure availability, and the validity of Islamic content circulating in cyberspace. The findings show that technology integration can increase motivation, interactivity, and access to learning, but also poses problems include the digital divide and inadequate teacher tech literacy, and the risk of invalid religious information. For this reason, an adaptive curriculum, innovative learning methods, and ongoing training for educators are needed. Collaboration between stakeholders plays a central role in designing a relevant, contextual, and effective Islamic Religious Education (PAI) education system that is contextual and effective in shaping the character of students with noble morals amidst the development of the digital era.